2018
DOI: 10.1177/8756479318791512
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Ultrasound Exposure: Knowledge, Attitudes, and Practices of Australasian Sonographers

Abstract: Introduction: While perceived as safe, diagnostic ultrasound has the potential to cause biological effects on the body tissues. The aim of this study was to evaluate knowledge, attitudes, and practices of Australasian sonographers on bioeffects and safety of ultrasound scanning. Methods: Focus groups were used to develop a questionnaire to explore knowledge, attitudes, and practices of ultrasound safety, which was then distributed to Australasian sonographers. Thematic (focus groups) and descriptive (questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Evidence to date has not provided sufficient evidence to prove ultrasound has harmful outcomes in humans. 32 However, research on animal tissue, in particular the brain, has shown adverse bioeffects such as tissue heating and cavitation. 24 It is therefore important to limit ultrasound exposure especially in the human foetus and neonates as these are more sensitive to potentially harmful bioeffects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence to date has not provided sufficient evidence to prove ultrasound has harmful outcomes in humans. 32 However, research on animal tissue, in particular the brain, has shown adverse bioeffects such as tissue heating and cavitation. 24 It is therefore important to limit ultrasound exposure especially in the human foetus and neonates as these are more sensitive to potentially harmful bioeffects.…”
Section: Discussionmentioning
confidence: 99%
“…24 It is therefore important to limit ultrasound exposure especially in the human foetus and neonates as these are more sensitive to potentially harmful bioeffects. [23][24][25]32 Both international and Australian guidelines advise that ultrasound imaging only be used when medically necessary and to keep scanning time to a minimum, as possible subtle and long-term effects in both foetal and adult tissue are not fully understood. 25,33 A small proportion of our participants (2.2%, 6/271) believed that ultrasound could cause cancer which may reflect participant's lack of understanding of the different imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…• Understand personal limits around work-related musculoskeletal disorders (WRMSD) and ask the patient to move to different positions where possible rather than using awkward positions just to get the best image. • Monitor TI and mechanical index (MI) settings on the machine and be mindful of scanning times with obstetrics [74] .…”
Section: Ultrasound (Us)mentioning
confidence: 99%
“…6 Sonographers' perceptions of patient safety focus on bioeffects and safe operation of ultrasound equipment. 7 However, there are other patient safety risks associated Australian sonographers' perceptions of patient safety in ultrasound imaging: Part 1 -identifying the main safety concerns, a qualitative study with sonography practice. Intimate examinations such as testicular and transvaginal (TV) examinations pose physical and psychological risk to patients.…”
Section: Introductionmentioning
confidence: 99%